A review of research progress on the application of bryophytes in the ecological restoration of mining areas of China - Qiao, Zhanrui; Lin, Xiaoai; Zhang, Tao; Luo, Shuigen; Wang, Cunbao; Zhou, Wei; Luo, Longzao (Frontiers in Environmental Science, 2025)
The process of mining is invariably associated with ecological and environmental challenges within the mining region, making ecological restoration efforts in these areas especially crucial. Bryophytes, acting as key pioneer species, exhibit distinctive advantages and potential for application in the ecological restoration of mining sites. This study offered a concise overview of the fundamental traits of bryophytes, as well as their classification and distribution in mining regions across China using literature synthesis and field surveys. It primarily explored the role bryophytes played in the ecological restoration of such areas, the selection of appropriate bryophyte species, and cultivation techniques through systematic analysis. Additionally, the case studies of bryophytes’ applications in ecological restoration within mining regions were analyzed. Results indicated that bryophytes in China’s mining areas were diverse and widely distributed. Notably, bryophytes contributed to soil improvement, vegetation recovery, and the monitoring and indication of heavy metal pollution, with most demonstrating a robust tolerance to these contaminants. Future research should focus on screening suitable bryophytes, refining cultivation methods, and investigating their interactions with soil microorganisms.